2015
DOI: 10.1093/nar/gkv392
|View full text |Cite
|
Sign up to set email alerts
|

TET1 is controlled by pluripotency-associated factors in ESCs and downmodulated by PRC2 in differentiated cells and tissues

Abstract: Ten-eleven translocation (Tet) genes encode for a family of hydroxymethylase enzymes involved in regulating DNA methylation dynamics. Tet1 is highly expressed in mouse embryonic stem cells (ESCs) where it plays a critical role the pluripotency maintenance. Tet1 is also involved in cell reprogramming events and in cancer progression. Although the functional role of Tet1 has been largely studied, its regulation is poorly understood. Here we show that Tet1 gene is regulated, both in mouse and human ESCs, by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 62 publications
3
33
0
1
Order By: Relevance
“…In addition, studies should explore the mechanisms behind TET1 overexpression at the early stage of differentiation. Fitting with our observations, overexpression of TET1 was recently described as a response to cell confluence and/or inhibition of cell proliferation (Neri et al., 2015). In our hands, HepaRG progenitors reduce their mitotic index 48 times after only 1 week of differentiation, as assessed by counting the percentage of mitotic nuclei with DAPI staining (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, studies should explore the mechanisms behind TET1 overexpression at the early stage of differentiation. Fitting with our observations, overexpression of TET1 was recently described as a response to cell confluence and/or inhibition of cell proliferation (Neri et al., 2015). In our hands, HepaRG progenitors reduce their mitotic index 48 times after only 1 week of differentiation, as assessed by counting the percentage of mitotic nuclei with DAPI staining (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…Due to the branched structure of SUMO-conjugated proteins, modification with a single SUMO can give rise to a migration shift in gel electrophoresis higher than the 10 kDa expected from the molecular weight of SUMO peptides. A main source of oxidative DNA attack in unperturbed mESCs is the action of the highly expressed TET1 and TET2 proteins (Koh et al, 2011;Neri et al, 2015;Zhang et al, 2016), as indicated by relatively high levels of the oxidative 5mC derivatives, 5-hydroxymethyl-C (5hmC), 5fC and 5caC in such cells (Fig 4D). Exposure of mESC to H 2 O 2 induced a significant enrichment of < 150-kDa XRCC1 conjugates (Fig 1F), suggesting that XRCC1, like TDG, can be modified by DNA lesions generated by general oxidative stress.…”
Section: Tdg and Xrcc1 Are Sumo Targets In Mescsmentioning
confidence: 99%
“…Exposure of mESC to H 2 O 2 induced a significant enrichment of < 150-kDa XRCC1 conjugates ( Fig 1F), suggesting that XRCC1, like TDG, can be modified by DNA lesions generated by general oxidative stress. A main source of oxidative DNA attack in unperturbed mESCs is the action of the highly expressed TET1 and TET2 proteins (Koh et al, 2011;Neri et al, 2015;Zhang et al, 2016), as indicated by relatively high levels of the oxidative 5mC derivatives, 5-hydroxymethyl-C (5hmC), 5fC and 5caC in such cells ( Fig 4D). High levels of full-length TET1 protein and its shorter isoform TET1s ( Fig 1G) in ESCs also correlated with higher steady-state levels of XRCC1-SUMO in comparison with mouse embryonic fibroblasts (MEFs; Fig 1D and G), indicating that TET-dependent base oxidation may promote XRCC1 SUMOylation.…”
Section: Tdg and Xrcc1 Are Sumo Targets In Mescsmentioning
confidence: 99%
“…TET1 is at its highest levels in ES cells (ESCs) and is down-regulated during differentiation. TET2 is also expressed in ESCs, and transcription of both genes is regulated by the pluripotency factors (9,10). Despite this, both TET1 and TET2 are also expressed through largely unknown mechanisms in differentiated tissues, although mice lacking TET1 or TET2 are viable and, asides from the TET2 effects on hematopoiesis, their definitive roles are mostly not clear (11)(12)(13).…”
mentioning
confidence: 99%